Taxonomic dependency of beta diversity for bacteria, archaea, and fungi in a semi-arid lake - Yuan, Haijun; Zhang, Weizhen; Yin, Huaqun; Zhang, Runyu; Wang, Jianjun (Frontiers in Microbiology, 2022)
Microbial beta diversity has been recently studied along the water depth in aquatic ecosystems, however its turnover and nestedness components remain elusive especially for multiple taxonomic groups. Based on the beta diversity partitioning developed by Baselga and Local Contributions to Beta Diversity (LCBD) partitioning by Legendre, we examined the water-depth variations in beta diversity components of bacteria, archaea and fungi in surface sediments of Hulun Lake, a semi-arid lake in northern China, and further explored the relative importance of environmental drivers underlying their patterns. We found that the relative abundances of Proteobacteria, Chloroflexi, Euryarchaeota and Rozellomycota increased towards deep water, while Acidobacteria, Parvarchaeota and Chytridiomycota decreased. For bacteria and archaea, there were significant (P < 0.05) decreasing water-depth patterns for LCBD and LCBDRepl (i.e., species replacement), while increasing patterns for total beta diversity and turnover, implying that total beta diversity and LCBD were dominated by species turnover or LCBDRepl. Further, bacteria showed a strong correlation with archaea regarding LCBD, total beta diversity and turnover. Such parallel patterns among bacteria and archaea were underpinned by similar ecological processes like environmental selection. Total beta diversity and turnover were largely affected by sediment total nitrogen, while LCBD and LCBDRepl were mainly constrained by water NO2--N and NO3--N. For fungal community variation, no significant patterns were observed, which may be due to different drivers like water nitrogen or phosphorus. Taken together, our findings provide compelling evidences for disentangling the underlying mechanisms of community variation in multiple aquatic microbial taxonomic groups.